Optimization of Physiochemical Conditions for Removal of Copper (II) Ions from Industrial Effluents Using Various Sorbents - Ghaffar, Abdul; Aslam, Muhammad (Asian Journal of Chemistry, 2010)
Removal of copper(II) ions from industrial effluents using different adsorbents such as activated carbon, brick kiln ash, tea waste, Ravi river sand and eggshells was studied to optimize the physicochemical conditions for maximum removal. The range of pH, temperature and concentration was so adjusted that it covers the physicochemical conditions of actual waste generated from industrial facilities. The initial and final concentration of copper was measured by atomic absorption spectroscopy. The residual concentration of copper in wastewater after adsorption was less than 1.0 mg/L, the released limit given in National Environment Quality Standards (NEQS). Maximum sorption (96-97%) of Cu(II) ions on activated carbon was achieved with (125 μm) particle size at 28ºC temperature, pH 7. Under optimized conditions and temperature range of 301-315 K, ΔH, ΔS and ΔG301 K for 100 ppm solution are -16.09 ± 02 to 85.46 ± 0.47 kJ/mol, -41.20 ± 0.07 to 246.93 ± 0.98 J/mol and -4.53 ± 0.62 to 11.26 ± 1.2 kJ/mol, respectively and for 150 ppm solution the thermodynamic entities are ΔH = -10.78 ± 0.09 to 57.03 ± 0.62 kJ/mol, ΔS = -22.75 ± 0.32 to 162.99 ± 2.03 J/mol and ΔG301 K = -3.79 ± 0.4 to 8.15 ± 0.9 kJ/mol. Based on this study, the removal efficiency of various sorbents may be enhanced by optimizing certain specified physiochemical conditions.